2018
DOI: 10.1002/stem.2834
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Bipotent Megakaryocytic-Erythroid Progenitors: Concepts and Controversies

Abstract: Hematopoietic stem and progenitor cells maintain blood formation throughout our lifetime by undergoing long- and short-term self-renewal, respectively. As progenitor cells progress through the hematopoiesis process, their differentiation capabilities narrow, such that the precursors become committed to only one or two lineages. This Review focuses on recent advances in the identification and characterization of bipotent megakaryocytic-erythroid progenitors (MEP), the cells that can further produce two complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 57 publications
3
36
1
Order By: Relevance
“…Our prior study 13 showed that numbers of BFU-E and CFU-E in MDS patients were obviously lower than healthy controls, which was confirmed in this study after expanding the sample size. In the present study, we further found that levels of HSCs and MEPs, which is a transitional stage of differentiation to both megakaryocytes and erythrocytes earlier than the BFU-E stage 29,30 , had already reduced in MDS. For a long time, the increased apoptosis of BM erythroid cells was considered to be responsible for ineffective erythropoiesis in MDS.…”
Section: Discussionsupporting
confidence: 74%
“…Our prior study 13 showed that numbers of BFU-E and CFU-E in MDS patients were obviously lower than healthy controls, which was confirmed in this study after expanding the sample size. In the present study, we further found that levels of HSCs and MEPs, which is a transitional stage of differentiation to both megakaryocytes and erythrocytes earlier than the BFU-E stage 29,30 , had already reduced in MDS. For a long time, the increased apoptosis of BM erythroid cells was considered to be responsible for ineffective erythropoiesis in MDS.…”
Section: Discussionsupporting
confidence: 74%
“…The model, unlike the mammalian model, depicts the formation of a polymerizing fibrin clot as the first step in repairing a vessel wall injury (b(iii)) followed by the binding of thrombocytes to collagen and a hard clot-forming with some cross-linking of thrombocytes and trapping of RBCs within the clot (b(iii,iv)) SOSLAU | 123 dearth of knowledge about their role in hemostasis and responses to platelet agonists. The progenitor cell for nonmammalian RBCs and thrombocytes is a bipotential thrombocytic/erythroid progenitor cell (TEPs) derived from self-renewing hematopoietic stem cells (HSCs; Svoboda & Bartunek, 2015;Svoboda et al, 2014;Tanizaki et al, 2015) in a sequence akin to the mammalian system that ultimately yields RBCs and megakaryocytes from the bipotential megakaryocyte/ erythroid progenitor cell (MEPs; Svoboda & Bartunek, 2015;Wong, Dolinska, Sigvardsson, Ekblom & Qian, 2016;Woolthuis & Park, 2016;Xavier-Ferrucio & Krause, 2018). Some evidence indicates that the mammalian bipotential MEP cell and its progeny cells, RBCs, and megakaryocytes, may also arise from alternate pathways (Woolthuis & Park, 2016;Xavier-Ferrucio & Krause, 2018).…”
Section: Evolution Of Mammalian Anucleate Blood Cellsmentioning
confidence: 99%
“…The progenitor cell for nonmammalian RBCs and thrombocytes is a bipotential thrombocytic/erythroid progenitor cell (TEPs) derived from self-renewing hematopoietic stem cells (HSCs; Svoboda & Bartunek, 2015;Svoboda et al, 2014;Tanizaki et al, 2015) in a sequence akin to the mammalian system that ultimately yields RBCs and megakaryocytes from the bipotential megakaryocyte/ erythroid progenitor cell (MEPs; Svoboda & Bartunek, 2015;Wong, Dolinska, Sigvardsson, Ekblom & Qian, 2016;Woolthuis & Park, 2016;Xavier-Ferrucio & Krause, 2018). Some evidence indicates that the mammalian bipotential MEP cell and its progeny cells, RBCs, and megakaryocytes, may also arise from alternate pathways (Woolthuis & Park, 2016;Xavier-Ferrucio & Krause, 2018). The ultimate production of RBCs and thrombocytes/platelets in both nonmammalian and mammalian systems is dictated by levels of TPO (thrombopoietin) and EPO (erythropoietin) that bind to analogous receptors stimulating similar signaling pathways in both cell types (Svoboda & Bartunek, 2015;Svoboda et al, 2014;Tanizaki et al, 2015;Woolthuis & Park, 2016;Xavier-Ferrucio & Krause, 2018).…”
Section: Evolution Of Mammalian Anucleate Blood Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematopoiesis, the hierarchical formation of different blood cell types from a common multipotent stem cell, involves complex cell state transitions and cell fate decision processes that are still incompletely understood (66)(67)(68)(69)(70). A multistep differentiation process involving successively restricted progenitor cell populations has been the dominant model to describe blood formation (71), although in some lineages restriction (to unipotency) may occur much earlier than previously thought (72).…”
Section: Hematopoietic Lineage Hierarchies Coupled With Single-cell Cmentioning
confidence: 99%